Indonesian Defense Diplomacy in Responding to China’s National Interest in South China Sea - Surryanto Djoko Waluyo (Jurnal Hubungan Internasional)
Economic interests dominating the interests of both claimant and non-claimant-states make the South China Sea conflict challenging to obtain a satisfactory solution for all parties. In protecting its financial security, mainly dependent on the South China Sea, China continues to exhibit aggressiveness and firmness in realizing its national interests in this area, thereby raising the conflict tension. This study analyzed Indonesia’s defense diplomacy to counter China’s national interests in the South China Sea. Defense diplomacy is expected to eliminate any obstacles hindering the achievement of the two countries’ national interests. This study utilized a descriptive qualitative method with primary data obtained through interviews with defense strategists, defense diplomacy actors, academics, and other supporting secondary data. This study discovered that China’s national interests in the South China Sea center on securing its economic interests and military modernization. Meanwhile, Indonesia’s national interests in the South China Sea concern the Exclusive Economic Zone (EEZ) waters. Maintaining the integrity of the Unitary Republic of Indonesia is one of its national interests. Thus, Indonesia’s defense diplomacy should be conducted through win-win cooperation to promote its national interests in responding to China’s national interests in the South China Sea.